Review on research progress and comparison of different residual stress strengthening methods for titanium alloys. (February 2023) - Xue, Nian-Pu; Wu, Qiong; Zhang, Yu; Li, Bian-Hong; Zhang, Yi-Du; Yang, Shuai; Zhu, Yu; Guo, Jian; Gao, Han-Jun
Highlights: These excellent titanium alloys are widely used in aerospace and aerospace field. Fatigue failure is mostly initiated on surface, threatening service reliability. Residual stress strengthening methods are developed, driven by aircraft lightweight. Strengthened stress transfers the fatigue crack and increases the fatigue lifetime. Various methods induce different residual stress, microstructures and roughness. Abstract: Titanium alloys are high-quality materials for aerospace parts with good thermal mechanical properties. Fatigue failure has been the most prominent problem, so surface strengthening technology is widely applied to improve fatigue life. In this paper, the recent progress of four typical strengthening methods is analyzed in detail, including MSP, USP, LSP and BSM. In the strengthening process, the RS induced by PD is the most significant variation, so the basic theory and measurement methods of RS are comprehensively summarized. Besides, grain refinement and dislocation density increase occur simultaneously, as well as the unfriendly phenomenon in the increase of surface roughness. Therefore, the progress in reaction mechanisms, influencing factors, strengthening effects and fatigue improvement of these four typical titanium alloy PD strengthening methods are explained, and various research methods and optimization strategies are summarized. In addition, the differences of strengthening methods are also compared. The latest advances of these methods are described, which will support the progress of strengthening technology.